2010
DOI: 10.1039/c003317k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mouse brain peptides using mass spectrometry-based peptidomics: implications for novel functions ranging from non-classical neuropeptides to microproteins

Abstract: Peptides are known to play many important physiological roles in signaling. A large number of peptides have been detected in mouse brain extracts using mass spectrometry-based peptidomics studies, and 850 peptides have been identified. Half of these peptides are derived from secretory pathway proteins and many are known bioactive neuropeptides which activate G protein-coupled receptors; these are termed "classical neuropeptides." In addition, 427 peptides were identified that are derived from non-secretory pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(200 citation statements)
references
References 109 publications
(258 reference statements)
11
188
0
1
Order By: Relevance
“…2,9,38−40 The formation of peptide fragments may come from in vivo peptide/protein processing, which are performed by intracellular proteolysis or by extracellular peptide decay after their release from neurons. 41 These processes are not fully understood yet. However, a line of evidence showed that many peptide fragments have distinct physiological functions, for example, activating particular receptors or inhibiting enzymes.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9,38−40 The formation of peptide fragments may come from in vivo peptide/protein processing, which are performed by intracellular proteolysis or by extracellular peptide decay after their release from neurons. 41 These processes are not fully understood yet. However, a line of evidence showed that many peptide fragments have distinct physiological functions, for example, activating particular receptors or inhibiting enzymes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, a line of evidence showed that many peptide fragments have distinct physiological functions, for example, activating particular receptors or inhibiting enzymes. 41,42 The identification of novel peptides therefore provided possible candidates for bioactive neuropeptides.…”
Section: ■ Discussionmentioning
confidence: 99%
“…1A), based on the list of reported neuropeptides, precursors and additional candidate [17,18] (see Supplementary Table 1). Current studies showed that neuropeptides are produced from their precursors by different neuropeptide-processing enzymes in different pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The database was constructed by first downloading a list of 2405 protein precursors [17,18] from the Uniprot database (http:// www.uniprot.org/, 7 July 2010) restricted to Euarchontoglires species. All these sequences were then submitted to an in silico peptide cleavage using custom made software written in Perl, according to the following template:…”
Section: Peptide Identification and Databasementioning
confidence: 99%
“…Although N-glycosylation occurs at predictable sites (-Asn-Xaa-Ser/Thr-, where Xaa is not Pro) and must be initiated in the endoplasmic reticulum, O-glycosylation sites cannot be predicted based on primary sequence (14,15). Based on earlier studies using [ 3 H]galactose, [ 35 SO 4 2Ϫ Met], and [ 35 S]Met, sulfated galactose-containing O-linked sugars are found on at least two Ser/Thr residues in the exon 16 region of PAM-1 (3,15). A prohormone convertase 1-mediated cleavage at the Lys-Lys site in exon 16 separates soluble PHM from membrane PAL, and at least one O-glycosylation site is found in each product.…”
mentioning
confidence: 99%